State of the question: Art in the teaching of Chemistry - Francisco José da Costa; Antônio Carlos Magalhães (Universidade Federal do Oeste da Bahia, 2020)
This article presents the State of the Question on the theme "Art in the Teaching of Chemistry". Its realization will make it possible to survey and analyze the productions found on the CAPES journals portal and publications of the Brazilian Chemical Society (BQS). The research presents commented studies published on the topic, highlighting the articulations and contributions of the languages of Art in the Teaching of Chemistry. The study concluded that the number of specific publications is small, and at the same time, loaded with evidence about the contribution of Art to make Chemistry Teaching reflective, dynamic and contextualized. It was also observed that the use of Art enables more active and critical involvement of students in classes, making them more protagonists in the process of teaching and learning the contents of Chemistry.